25-hydroxyvitamin D status in patients with alopecia areata - Erpolat, Seval; Sarifakioglu, Evren; Ayyildiz, Abdullah (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Alopecia areata (AA) is a T cell-mediated autoimmune disease that causes inflammation around anagen-phase hair follicles. Insufficient levels of vitamin D have been implicated in a variety of autoimmune diseases. Aim : To investigate the status of serum 25-hydroxyvitamin D (25(OH)D) in patients with AA, serum 25(OH)D concentrations were compared between AA patients and healthy controls and thus determine if a possible association exists between serum 25(OH)D levels and AA. Material and methods : The study comprising 41 patients diagnosed with AA and 32 healthy controls was conducted between October 2010 and March 2011. The serum vitamin D levels of the study group were determined by high performance liquid chromatography. Serum levels of calcium, phosphorus, alkaline phosphatase, and parathyroid hormone were also evaluated. Results : The study was based on 41 patients aged between 20 and 50 (mean: 32.8 ±7.5). The control group included 32 healthy persons aged between 20 and 51 (mean: 32.7 ±7.5). Serum 25(OH)D levels in patients with AA ranged from 5.0 to 38.6 ng/ml with a mean of 8.1 ng/ml. Serum 25(OH)D levels in healthy controls ranged from 3.6 to 38.5 ng/ml with a mean of 9.8 ng/ml. There was no statistically significant difference in the serum vitamin D level between AA patients and healthy controls (p > 0.05). Conclusions : Deficient serum 25(OH)D levels are present in patients with AA. However, considering the high prevalence of vitamin D deficiency in Turkey, no difference was noted between AA patients and controls.